(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper provides a detailed understanding behind the motives of people committing crimes. Researchers have named ―the people committing crime, where the crimes were minimal and confined to a particular area of administration‖ as Grass Eaters. People involved in white collar crimes and which has spread in almost all fields of business are termed as Meat Eaters. With the advent of technology and growth of education, white collar crimes are on the rise, being protected by professionals finding loopholes in the judiciary and support from the government indirectly.This has created a nexus where people from almost all walks of life have started forming group to do white collar crimes and being protected by professionals in law. This has led to a situation where the small timers have become white collar criminals. Talking about the prevalence of white collar crimes in India, they are spreading like a rapid fire in every sphere of society. Though corruption, one of the species of white collar crimes, has been the most talked about issue in all spheres-social, economic and political, not much stringent stepsactions have been taken to curb this menace. Therefore the concern of this paper is to define white collar crime, study its historical development and formulate tentative solutions for eradicating the problem.